Heaping on Dividends: The Role of Dividend Size and Information Uncertainty. Issue 1 (2nd January 2020) - Jakob, Keith; Nam, Yoonsoo
Abstract: The authors examine whether a cognitive bias influences dividend policy. They find that managers use a heaping heuristic when choosing the amount of their firm's dividend. Heaping is a human error or bias to round numbers even though precise values are desired. This bias leads to dividend distributions clustered at specific amounts. Dividend size and the level of information uncertainty faced by management help explain the likelihood of heaping. The authors also observe that heaped dividends are "sticky" and altered less frequently, and when there is a dividend change, heaped dividends are more often switched to another heaped amount.